2006
DOI: 10.1158/1078-0432.ccr-06-0944
|View full text |Cite
|
Sign up to set email alerts
|

Improving Antitumor Immune Responses by Circumventing Immunoregulatory Cells and Mechanisms

Abstract: Although numerous immunotherapeutic strategies have been studied in patients with cancer, consistent induction of clinical responses remains a formidable challenge. Cancer vaccines are often successful at generating elevated numbers of tumor-specific T lymphocytes in peripheral blood, however, despite this, tumors usually continue to grow unabated. Recent evidence suggests that endogenous regulatory cells, known to play a major role in the induction of immune tolerance to self and prevention of autoimmunity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 175 publications
(40 reference statements)
0
63
0
2
Order By: Relevance
“…Therefore, accumulation of MDSC and Treg in tumor tissue is crucial for tumor immune escape and supposed to be the target of immunotherapy (11). However, little is known about the natural signals in the tumor microenvironment responsible for inducing accumulation and maintaining residence of MDSC and Treg cells in the tumor tissues.…”
Section: Cd25mentioning
confidence: 99%
“…Therefore, accumulation of MDSC and Treg in tumor tissue is crucial for tumor immune escape and supposed to be the target of immunotherapy (11). However, little is known about the natural signals in the tumor microenvironment responsible for inducing accumulation and maintaining residence of MDSC and Treg cells in the tumor tissues.…”
Section: Cd25mentioning
confidence: 99%
“…In addition to CD25 depletion and CTLA4 blockade, other approaches, including anti-GITR antibody therapy (Ko et al, 2005), antibody blockade of PD-1 (Iwai et al, 2002;Curiel et al, 2003;Hirano et al, 2005) and neutralization of immunosuppressive cytokines, such as IL-10, TGF-b, IL-13 and vascular endothelial growth factor (Lizee et al, 2006), have been assessed for their ability to reverse Treg cell-mediated suppression of antitumour responses. However, it is likely that such non-targeted approaches will share some or all of the problems associated with CD25 depletion and anti-CTLA-4 treatment.…”
Section: The Benefit Of Depletion or Inhibition Of Treg Cells Or Theimentioning
confidence: 99%
“…Several other tumour-infiltrating immune cells have been reported to support tumour growth, including tumour-associated macrophages, and immature myeloid and dendritic cells (Lizee et al, 2006). Also, it has been reported that specific functional aspects of innate immune cells are pivotal for intestinal homeostasis, inflammation, and tumorigenesis.…”
Section: Immune Cells and Adipocytes Modulating Tumour Growthmentioning
confidence: 99%